Manas : kyrgyz èlinin baatyrlyk èposu = Manas : kirgizskij geroičeskij èpos. Kitep 3. (Ėpos narodov SSSR, 1990)
English summary.
Keywords: Manas; eepokset; kansalliseepokset; kirgiisit; sankarit; epos; nationalepos; kirgizer; hjältar